KARYOMORPHOLOGY OF THE PHILIPPINE ROCK GOBY, Glossogobius giuris (GOBIIDAE) FROM LAKE TAAL AND SOME RIVERS OF CAVITE, LUZON ISLAND - JIMMY T MASAGCA; JOSE A. ORDONEZ (SEAMEO BIOTROP, 2003)
The karyomorphology of Glossogobius giuris (Gobiidae) obtained from Lake Taal and some rivers of Cavite in Luzon Island, Philippines was described. Metaphase chromosome analysis (colchicine-sodium citrate-Carnoy's fixation-Giemsa staining procedures) of the hematopoitetic cells in the anterior kidneys revealed that the diploid chromosome number was 2n=46 (46A). Fundamental Number (FN) is also 46, since all chromosomal morphology were acrocentrics without any distinguishable heteromorphic pair of chromosomes in the metaphase spreads from both dry and wet preparations. This study confirms previous reports on the chromosomal sets of G. giuris from India. Keywords : Philippines / Lake Taal / Genetics / Karyomorphology / Glossogobius giuris